MODEL PENANGANAN PERILAKU MALADAPTIF ANAK BERBASIS PANTI - Mayaut, Flores George; Istanto, Istanto (Jurnal Insani, 2021)
This study discusses the role of social workers in handling maladaptive behavior in children at PSAA Putra Utama 2 North Jakarta" This research is descriptive analysis. The objectives are (1) to find out the problem of maladaptive behavior of children in social institutions; (2) to determine the role of social workers in dealing with maladaptive behavior of children in social institutions; (3) to find out the results of the implementation of the role of social workers in dealing with maladaptive behavior of children in social institutions. Maladaptive behavior is bad behavior displayed by someone that is not in accordance with the environment or what is desired by the community where the person lives. This can happen because of a person's inability to interpret something that happens to him. Through this research, it is hoped that it can contribute ideas in enriching the concept of social work practice, especially regarding social work interventions in dealing with children's maladaptive behavior and can contribute ideas to solving problems related to children's maladaptive behavior.